Diagnostic Criteria for the Painful Swollen Pediatric Knee: Distinguishing Septic Arthritis From Aseptic Effusion in a Non-Lyme Endemic Area - Thomas, Claudia S.; Schiffman, Corey J.; Faino, Anna; Bompadre, Viviana; Schmale, Gregory A. (Frontiers in Surgery, 2021)
Purpose The child with a painful swollen knee must be worked up for possible septic arthritis; the classic clinical prediction algorithms for septic arthritis of the hip may not be the best models to apply to the knee. Materials and Methods This was a retrospective case-control study of 17 years of children presenting to one hospital with a chief complaint of a painful swollen knee, to evaluate the appropriateness of applying a previously described clinical practice algorithm for the hip in differentiating between septic and aseptic causes of a painful knee effusions. Diagnoses of true septic arthritis, presumed septic arthritis, and aseptic knee effusion were established, based upon cultures of synovial fluid, blood cultures, synovial cell counts, and clinical course. Using a logistic regression model, disease status was regressed on both demographic and clinical variables. Results 122 patients were included: 51 with true septic arthritis, 37 with presumed septic arthritis, and 34 with aseptic knee effusion. After applying a backwards elimination, age less than 5 years and C-reactive protein greater than 2.0 mg/dl remained in the model, and predicted probabilities of having septic knee arthritis ranged from 15% for the lowest risk to 95% for the highest risk. Adding a knee aspiration including percent polymorphonucleocytes substantially improved overall model performance, lowering the lowest risk to 11% while raising the highest risk to 96%. Conclusions This predictive model suggests that the likelihood of pediatric septic arthritis of the knee is greater than 90% when both age less than 5 years and CRP > 2.0 mg/dl are present in a child with a painful swollen knee, though in the absence of these factors, the risk of septic arthritis remains over 15%. Knee aspiration for those patients would be the best next step.